Circulating tumor DNA quantity is related to tumor volume and both predict survival in metastatic pancreatic ductal adenocarcinoma. Issue 5 (13th August 2019) - Strijker, Marin; Soer, Eline C.; de Pastena, Matteo; Creemers, Aafke; Balduzzi, Alberto; Beagan, Jamie J.; Busch, Olivier R.; van Delden, Otto M.; Halfwerk, Hans; van Hooft, Jeanin E.; van Lienden, Krijn P.; Marchegiani, Giovanni; et al.
Abstract : Circulating tumor DNA (ctDNA) is assumed to reflect tumor burden and has been suggested as a tool for prognostication and follow‐up in patients with metastatic pancreatic ductal adenocarcinoma (mPDAC). However, the prognostic value of ctDNA and its relation with tumor burden has yet to be substantiated, especially in mPDAC. In this retrospective analysis of prospectively collected samples, cell‐free DNA from plasma samples of 58 treatment‐naive mPDAC patients was isolated and sequenced using a custom‐made pancreatobiliary NGS panel. Pathogenic mutations were detected in 26/58 (44.8%) samples. Cross‐check with droplet digital PCR showed good agreement in Bland–Altman analysis ( p = 0.217, nonsignificance indicating good agreement). In patients with liver metastases, ctDNA was more frequently detected (24/37, p  < 0.001). Tumor volume (3D reconstructions from imaging) and ctDNA variant allele frequency (VAF) were correlated (Spearman's ρ = 0.544, p  < 0.001). Median overall survival (OS) was 3.2 (95% confidence interval [CI] 1.6–4.9) versus 8.4 (95% CI 1.6–15.1) months in patients with detectable versus undetectable ctDNA ( p = 0.005). Both ctDNA VAF and tumor volume independently predicted OS after adjustment for carbohydrate antigen 19.9 and treatment regimen (hazard ratio [HR] 1.05, 95% CI 1.01–1.09, p = 0.005; HR 1.00, 95% CI 1.01–1.05, p = 0.003). In conclusion, our study showed that ctDNA detection rates are higher in patients with larger tumor volume and liver metastases. Nevertheless, measurements may diverge and, thus, can provide complementary information. Both ctDNA VAF and tumor volume were strong predictors of OS. Abstract : What's new? Circulating tumor DNA (ctDNA) attracts much interest as a possible prognostic tool for cancer. Here, the authors showed that the quantity of ctDNA correlated strongly with tumor volume in metastatic pancreatic ductal adenocarcinoma (mPDAC). They conducted a retrospective analysis using samples collected from 58 untreated mPDAC patients. For this study, the authors designed a pancreatobiliary NGS panel, which they used to test the patients' cell‐free DNA, along with droplet digital PCR. Both ctDNA variant allele frequency and tumor volume predicted overall survival, they found.